Investigation of Different Gastrointestinal Parasites in Stray Dogs in Garmian Administration Area, Kurdistan Region, Iraq - Wahab, Mohammed Abdulkareem (Sulaimani Journal for Pure and Applied Sciences, 2022)
The aims of the study were to diagnose and investigate the prevalence of different gastrointestinal parasites species in dog feces in various locations of the study area. The study was conducted between April and July 2021, during this period a total of 269 fresh fecal samples were collected from adult stray dogs of both gender in public areas from eleven municipalities of Garmian administration, then they were directly processed and analyzed using different standard coprological techniques: screening by dissecting microscope, direct fecal smear with normal saline and Lugol’s solution staining, centrifugal sedimentation, and centrifugal flotation. The results of the study showed that 172 (63.94%) of the total examined dogs were found to be infected with one or more gastrointestinal parasite species (protozoa, cestodes, nematodes, and trematode) with the prevalence 57.620% (155/269), 28.252% (76/269), 10.037% (27/269), and 0.371% (1/269) respectively, as well as indicated that there were statistically significant differences among these rates (p<0.05). The detected parasites significantly differ in their prevalence include: Echinococcus granulosus 21.933% (59/269), Cystoisospora canis 21.561% (58/269), Sarcocystis spp. 12.639% (34/269), Giardia spp. 11.524% (31/269), Ancylostoma canis 5.204% (14/269), Cryptosporidium spp. 4.089% (11/269), Eimeria spp. 5.204% (14/269), Dipylidium caninum 3.345% (9/269), Mesocestoid lineatus 2.973% (8/269), Balantidium spp. 2.602% (7/269), Toxocara canis 1.486% (4/269), Trichuris vulpis 1.486% (4/269), Uncinaria stenocephala 1.115% (3/269), Toxascaris leonina 0.743% (2/269) and Nanophyetus salmincola 0.371% (1/269). This was the first record of these parasites in stray dogs from Garmian Administration area/Iraqi Kurdistan region, in which the types of infection showed that 62.209% (107/172) dogs had single, and 37.790% (65/172) mixed infections which included; double 25.581% (44/172), triple 11.046% (19/172), and quadruple 1.162% (2/172), these types of infection were showed statistically significant difference among each other (p<0.05). The highest prevalence of intestinal infection among dogs was found in May at 72% (36/50) followed by 65.625% (63/96) in April, 61.29% (38/62) in June, and the lowest was 54.098% (33/61) in July with significant difference among them (p<0.05). The results also revealed that all sampled locations examined were positive for the majority of the above-identified parasites, the most prevalent location was Kifri district 100 % (19/19), followed by Qorato sub-district 76.47% (13/17), Shekh Taweel sub.district 75% (12/16), Khanaqin district 69.696% (23/33), Rizgari sub-district 65% (13/20), Pebaz (Bawanur) sub-district 64.285% (18/28), Kalar district 62.5% (20/32), Serqela sub-district 61.29% (19/31), Maidan sub-district 58.333% (14/24), Awaspi sub.district 52.38% (11/21), while Kokiz sub-district was appeared to be the lowest prevalence rate of infection 35.714% (10/28), the statistical analysis showed significant differences in infection rates among these locations (p<0.05).It was that all the identified parasites were recorded for the first time in this area and they were potentially hazardous zoonotic agents, so it was recommended that human beings should avoid fecal contamination of stray dogs in public areas, moreover serious attention by the veterinarians, municipality of the study area and public health service is necessary to generate awareness of these parasites' potential threat.
Keywords: Dogs,Garmian Administration/Iraq; Gastrointestinal parasites; prevalence; public health